Kepuasan Pernikahan dan Conflict Resolution pada Pasangan Long Distance Marriage - Laelatul Anisah; Cahya Milia Tirta Safitri; Heppy Syawalina Kusuma (Departement of Mathematics Education, 2023)
Long Distance Marriage or also called long-distance marriage, is a familiar phenomenon, including in Indonesia. Long Distance Marriage describes a situation where couples are physically separated. One partner has to go elsewhere for specific purposes, such as work, or the other partner has to stay at home or in their area of ​​origin. Long-distance marriages also cause many wives to experience loneliness because their husbands have left them for months. Physical separation from people considered close is often a painful experience and can affect almost every aspect of life.This study aims to determine the relationship between marital satisfaction and conflict resolution in long-distance marriage couples. This study uses a quantitative correlational method. The data collection technique used the purposive sampling method, determining the sample with specific considerations. The number of participants in this study was 66 out of a total population of 260, with criteria including Married men/women, under 40 years of age and undergoing long-distance marriages.The results of this study indicate that there is a relationship between marital satisfaction and conflict resolution. This is indicated by the coefficient values ​​of the two variables, namely Rxy = 0.246 with FCount = 4.123 (FCount>3.986) and P = 0.046 (p <0.05). There is a positive relationship between marital satisfaction and conflict resolution. This is indicated by the value of the correlation coefficient on marital satisfaction and conflict resolution variables, which is 6.1%. This means that the higher the marital satisfaction, the higher the level of conflict resolution in long-distance marriage couples. Vice versa, the lower the marital satisfaction, the lower the level of conflict resolution in long-distance marriage couples.